Women and men in the Caribbean Community : facts and figures, 1980-2001 (CCS GeorgetownGY, 2003)
Deals with statistics and indicators on key social and gender issues of particular concern to the CARICOM region. Focuses especially on the areas of health, education and work.
Keywords: WOMEN